2016
DOI: 10.3109/09687637.2016.1167166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a five-day training programme on opioid substitution therapy in India

Abstract: Aims: In India, opioid substitution therapy (OST) has been scaled-up in the recent years for HIV prevention among injecting drug users. This study aimed to assess the change in knowledge and attitude of the OST staff who underwent a five-day training programme on OST. Methods: Using a ''pre-test post-test'' design, routine data collected from 267 staff who underwent the OST training was analysed. The staff composition was: doctors (n ¼ 42, 15.7%), nurses (n ¼ 49, 18.4%), counsellors (n ¼ 45, 16.9%) and other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The Indian OST guidelines 25 for provision of buprenorphine recommend a lower daily maintenance dose of 8-12 mg compared to analogous guidelines in other countries 44,45 . While studies in many settings show that higher buprenorphine dose is associated with improved adherence and retention 4651 , this recommendation in part was borne out of the earlier studies in India showing high retention with lower doses of buprenorphine 24,3335,52,53 . However, even by the Indian OST guidelines, more than three quarter of PWID at ICCs received less than 8 mg of buprenorphine daily.…”
Section: Discussionmentioning
confidence: 99%
“…The Indian OST guidelines 25 for provision of buprenorphine recommend a lower daily maintenance dose of 8-12 mg compared to analogous guidelines in other countries 44,45 . While studies in many settings show that higher buprenorphine dose is associated with improved adherence and retention 4651 , this recommendation in part was borne out of the earlier studies in India showing high retention with lower doses of buprenorphine 24,3335,52,53 . However, even by the Indian OST guidelines, more than three quarter of PWID at ICCs received less than 8 mg of buprenorphine daily.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] A situation assessment conducted among 42 OST centers, supported by National AIDS Control Organization (NACO), reported that the mean dose of buprenorphine was 6 mg/day and 89% patients reported that they were satisfied with the dose. [ 22 ] The lower dose requirement of Indian patients is also reflected with methadone. The multicentric study on methadone[ 14 ] also reported the average dose of methadone required for each patient to be 40 mg/day, a dose much less than the minimum recommended dose of 60 mg/day in most international studies and guidelines.…”
Section: Dose Requirements Of Opioid Substitution Therapy Medicinesmentioning
confidence: 99%
“…Sizeable proportion of clients (35%–40%) reported withdrawal and craving and used illicit opioids (28%). [ 36 ] There was an urgent need to improve the capacity of the staff working in OST centers to cater to the rapid scale-up of NACO OST Programme.…”
Section: Journey Of Opioid Substitution Therapy In Indiamentioning
confidence: 99%
“…A study conducted to assess the effectiveness of induction training showed a significant improvement in the knowledge of all the staff cadres over the 5-day training. [ 39 ] We have also developed an online OST training for NACO in collaboration with the Public Health Foundation of India to further standardize the training. In keeping with the knowledge and experience of OST in India, we also have updated the NACO clinical practice guidelines for buprenorphine-based OST.…”
Section: Journey Of Opioid Substitution Therapy In Indiamentioning
confidence: 99%